Views of the A. Konysskyi on determination of the form and price of claim and amount of remuneration for court costs and its trial support - Александров, Олексій Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This article analyzes the views of the famous Ukrainian social and cultural activist, lawyer, writer A.J. Konyskyi (1836-1900) on issues related to the procedure for determining the form and price of the claim and compensation for court costs and providing it by trial it in the second half of the nineteenth century, and their solutions. The author also shows their relevance to contemporary legal science.